LEADERSHIP AND TEAM MANAGEMENT (American Journal of Business Management, Economics and Banking, 2025)
In today's world, leadership and teamwork are very important for success. This article tells you about leadership and how to make a good team. It tells you about the main rules, tools, and new ways to be a good leader and make a good team that works well.